CRP Interacts Specifically With Sxy to Activate Transcription in Escherichia coli - Søndberg, Emilie; Sinha, Anurag Kumar; Gerdes, Kenn; Semsey, Szabolcs (Frontiers in Microbiology, 2019)
Horizontal gene transfer through natural competence is an important driving force of bacterial evolution and antibiotic resistance development. In several Gram-negative pathogens natural competence is regulated by the concerted action of cAMP Receptor Protein (CRP) and the transcriptional co-regulator Sxy through a subset of CRP binding sites (CRP-S sites) at genes encoding competence factors. Despite the wealth of knowledge on CRP’s structure and function it is not known how CRP and Sxy act together to activate transcription. In order to get an insight into the regulatory mechanism by which these two proteins activate gene expression, we performed a series of mutational analyses on CRP and Sxy. We found that CRP contains a previously uncharacterized region necessary for Sxy dependent induction of CRP-S sites, here named ‘Sxy Interacting Region’ (SIR) encompassing residues Q194 and L196. Lost promoter induction in SIR mutants could be restored in the presence of specific complementary Sxy mutants, presenting evidence for a direct interaction of CRP and Sxy proteins in transcriptional activation. Moreover, we identified constitutive mutants of Sxy causing higher levels of CRP-S site promoter activation than wildtype Sxy. Both suppressor and constitutive mutations are located within the same area of Sxy.